Effect of exercise training on heart rate variability in patients with obstructive sleep apnea: A randomized controlled trial. (22nd May 2019) - Berger, Mathieu; Raffin, Jérémy; Pichot, Vincent; Hupin, David; Garet, Martin; Labeix, Pierre; Costes, Frédéric; Barthélémy, Jean‐Claude; Roche, Frédéric
Abstract : While obstructive sleep apnea (OSA) increases chemoreflex, leading to an autonomic dysfunction in the long term, no studies have yet assessed the potential benefit of exercise on cardiac autonomic activity in these patients. The aim of this study was to evaluate potential improvement in cardiac autonomic function (CAF) measured through heart rate variability (HRV) after a 9‐month physical activity program in patients with OSA. Seventy‐four patients with moderate OSA, aged 40‐80 years, were randomly assigned to an exercise group (n = 36, 3 × 1 h/wk) or a control group (n = 38) during 9 months. Linear and nonlinear HRV parameters were measured during night using a Holter ECG. After 9 months, mean R‐R intervals increased in the exercise group without any changes in HRV parameters, while controls decreased global (standard deviation of normal‐to‐normal intervals, total power) and parasympathetic (root mean square successive difference of N‐Ns, very low frequency, high frequency, and standard deviation of the instantaneous beat‐to‐beat variability) indices of HRV ( P < 0.05 for all). Significant correlations with moderate effect size were found between changes in apnea severity and changes in R‐R intervals ( P < 0.05). Improvement in moderate‐to‐vigorous physical activity was also correlated to improvement in nocturnal oxygen parameters ( P < 0.05). In conclusion, supervised community physical activity may prevent a decline in nighttime CAF observed in nontreated community‐dwelling patients with moderate OSA over a 9‐month period. Thus, beyond apnea‐hypopnea index improvement, exercise may be cardioprotective in OSA patients through bradycardia, CAF preservation, and VO2peak increase.